Cost-effectiveness analysis of inavolisib combined with palbociclib plus fulvestrant in PIK3CA-mutated HR+/Her2− advanced breast cancer in China - Huang, Weiwei; Li, Cijuan; Huang, Yuanqing; Wang, Chang; Zhang, Yingxin; Lin, Yingtao (Frontiers in Pharmacology, 2026)
BackgroundInavolisib, a selective PI3Kα inhibitor, combined with palbociclib and fulvestrant, has demonstrated significant clinical benefit in PIK3CA-mutated hormone receptor–positive/human epidermal growth factor receptor 2–negative (HR+/HER2−) advanced or metastatic breast cancer (ABC/MBC). However, its cost-effectiveness in China remains unclear.MethodsA partitioned survival model with three health states—progression-free survival (PFS), progressive disease (PD), and death—was developed to evaluate inavolisib plus palbociclib-fulvestrant versus palbociclib-fulvestrant alone from the Chinese healthcare perspective. Survival data were derived from the phase III INAVO120 trial, while costs and utility values were obtained from local sources and literature. The model estimated total costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). Deterministic and probabilistic sensitivity analyses (DSA and PSA) and scenario analyses were conducted to assess model robustness and the impact of drug price and time horizon variations.ResultsInavolisib combination therapy increased total costs ($194306.06 vs. $55938.19) and QALYs (2.999 vs. 1.744), resulting in an ICER of $110260.53/QALY, exceeding the Chinese willingness-to-pay (WTP) threshold of $40271.00/QALY. ICER was most sensitive to PFS utility and drug cost. Scenario analyses indicated that inavolisib would become cost-effective if its price decreased by approximately 88.53%.ConclusionWhile inavolisib plus palbociclib-fulvestrant significantly prolongs PFS and OS in PIK3CA-mutated HR+/HER2− ABC/MBC, it is not cost-effective at current prices in China. Strategic price adjustments or reimbursement negotiations are essential to improve economic feasibility and inform clinical and policy decisions.